MARKETING RESEARCH OF THE DOMESTIC MARKET OF MEDICINES APPLIED IN STOMATOLOGY - T.P. Zarichnaia (Ukrainian Medical Stomatological Academy, 2015)
Dental diseases are the most common human diseases. So, incidence of caries in adults constitutes 90- 92%, gum diseases (gingivitis, periodontal disease) are diagnosed in 92% of cases. Only 8-9% of the adult population have healthy teeth and gums. It is actual to provide inhabitants with qualitative and effective medicines, which are used in dentistry in time. The purpose of the work was marketing research of the domestic market of medicines applied in stomatology, including carrying out the analysis of assortment and company structure of the studied segment of the market, studying of competitiveness of producers who deliver drugs of the specified action, definition of the most effective of them by method of the qualimetric analysis. The data of "Compendium" and "State register of medicinal facilities of Ukraine" was used for the research. The studies of assortment structure have been conducted in accordance with the "State register of medicinal facilities of Ukraine", that registers 64 names of medications with marked action. It has been established that market segment represents 16 (25%) of the original medicines and 48 (75%) generics. The number of mono-medicines is 32 (50%) and the combined ones − 32 (50%). In the studying group it was equal. The assortment of these drugs submitted external use of medicinal forms consisted of solid, liquid, soft matter, aerosols and sprays. Analysis of companies' structure of the studied market segment showed that 59.4% of drugs with marked actions were produced by 12 domestic pharmaceutical enterprises; 40.6% came from 12 foreign countries, 18 pharmaceutical companies (most of them were from Poland and India). Determination of competitiveness level of suppliers of medications for using in stomatology on the Ukrainian market showed that the main competition was opened among 6 foreign companies from Germany, Netherlands, Poland, Austria, Bulgaria and among 7 domestic ones, which provided the investigated market segment with the phyto drugs (К = 0,92). Also, there is high competition between domestic companies that supply medicinal herbs (K = 0.80). Calculations of the market share occupied by each of the pharmaceutical companies allowed to determine that the largest share in the investigated segment was occupied by domestic pharmaceutical companies such as "Ternopharm" Ternopil, "Liktravy" Zhytomyr and "Lubnyfarm" Lubny. Synmedik Laboratories, India occupies the largest part of this segment among foreign producers. The most effective stomatologic drugs such as synthetic, herbal medicines and propolis, medicinal herbs have been identified by the method of qualimetric analysis. It has been established that among synthetic drugs the most competitive and rational drugs are drugs from Hexetidine (K = 1) group, the most effective is Heksoral. Kamistad gel H (K = 1.00), Stomatofit (K = 0.92), Rotokan (K=0.83) are the most rational among phyto drugs. Leaves of Salvia are the most efficient among the medicinal plants in terms of qualimetric analysis. It is recommended to pay attention to the results of the research for more effective market saturation of competitive drugs in the studying group.